The Assessment of the Disproportion’s in Populations Income Distribution in Lithuania - Misiūnas, Algimantas; Moščinskas, Petras (Ekonomika, 1995)
In Lithuania the main data source for the research in the field of incomes is sampling of household data. At this moment in Lithuania are examined 1500 families in which are 4100 members of the families. For a long period of time in Lithuania was used an interval method for grouping the research data, but recently the decile method came into use. In our researches we evaluated the conformity of interval distribution of one family’ member’s income rate with log-normality law, and also the possibilities of forecasting based on possible mean numbers of incomes and the rate of dispersion in the long-term period.The researches of income’s distribution showed that asymmetry is not basic. Lorenz’s curve Gini coefficient gave the possibility to evaluate the inequality of income’s.